A Systematic Literature Review for the Topic of Blockchain Technology and Educational Systems in the Gulf Cooperation Council (GCC) - Baraa Al-Samarai; Jorge Morato (Applied Sciences)
As the world is shifting into a compelling environment of digitalization and transparency, it is important to figure out the criteria that would enhance those kinds of changes. For as much as those changes require constant advocacy and control, one can see the results that would benefit society as whole. Education is an important aspect in the world, and the digital world has obtained a piece of the educational digital sect. Yet, with the ongoing online learning and distance learning that have been roaming the world, plenty of disturbances within society have occurred and with that multiple solutions have emerged as a consequence. This research is based on an important solution that has conquered the international world, except for some parts of the region, which is why, through our provided methodologies and results, it has been concluded that blockchain, as a digital and educational option, is something that would not only provide more transparency but also more security and beneficiaries within the educational system. This study uniquely focuses on the GCC region, highlighting the specific challenges and opportunities in implementing blockchain technology in education. Unlike previous reviews that take a global perspective, this research examines the cultural, regulatory, and infrastructural barriers in GCC countries.